Persons Sentenced to Death and Their Last Statement: Presence and Absence of Techniques of Neutralization - van Baak, Carlijn (Homicide studies, 2025)
Extant research suggests that offenders use techniques of neutralization. Using qualitative analysis, we examine the presence or absence of techniques of neutralization among the population of persons sentenced to death for homicide in Texas during their last statement before execution between 1982 and 2022 (N = 578) and how such techniques overlap with other emergent themes. Results indicate that only a small portion (25%) of those convicted of homicide justify their actions when faced with execution, while often simultaneously expressing gratitude or guilt.